The dimethylarginine (ADMA)/nitric oxide pathway in the brain and periphery of rats with thioacetamide-induced acute liver failure: Modulation by histidine. (September 2015) - Milewski, Krzysztof; Hilgier, Wojciech; Albrecht, Jan; Zielińska, Magdalena
Highlights: Acute liver failure (ALF) raises blood and brain dimethylarginine (ADMA). ALF reduced the brain and liver activity of ADMA-degrading enzyme, DDAH. His i.p. reversed the changes in brain ADMA content, and DDAH and NOS activities. ALF-induced inflammatory response in blood and brain was not affected by His. His increased the total antioxidant capacity in brain cortex, but not in blood. Abstract: Hepatic encephalopathy (HE) is related to variations in the nitric oxide (NO) synthesis and oxidative/nitrosative stress (ONS), and asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthases (NOSs). In the present study we compared the effects of acute liver failure (ALF) in the rat TAA model on ADMA concentration in plasma and cerebral cortex, and on the activity and expression of the ADMA degrading enzyme, dimethylarginine dimethylaminohydrolase (DDAH), in brain and liver. ALF increased blood and brain ADMA, and the increase was correlated with decreased DDAH activity in both brain and liver. An i.p. administration of histidine (His), an amino acid reported to alleviate oxidative stress associated with HE (100 mg/kg b.w.), reversed the increase of brain ADMA, which was accompanied by the recovery of brain DDAH activity (determined ex vivo ), and with an increase of the total NOS activity. His also activated DDAH ex vivo in brain homogenates derived from control and TAA rats. ALF in this model was also accompanied by increases of blood cyclooxygenase activity and blood and brain TNF-α content, markers of the inflammatory response in the periphery, but these changes were not affected by His, except for the reduction of TNF-α mRNA transcript in the brain. His increased the total antioxidant capacity of the brain cortex, but not of the blood, further documenting its direct neuroprotective power.